Kinerja Penyuluh Pertanian Di Wilayah Kerja Badan Pelaksana Penyuluhan Pertanian Perikanan dan Kehutanan (BP4K) Kabupaten Kepulauan Sangihe - Rudy L. Janis; Lyndon R.J. Pangemanan; Olly E.H. Laoh; Ribka M. Kumaat (COCOS, 2014)
ABSTRACKRudy Lantang Janis Performance of Agricultural Extension in the Working Area of the Implementing Agency of Agricultural Fisheries and Forestry (BP4K) Sangihe Islands Regency Under the guidance of Lindon R. J. Pangemanan as Chairman, O. Esry laoh and Ribka M. Kumaat as membersThe objective of the research to analyse performance, education, skill, discipline work ethos, number of extension wokers, agricultural extension and personnel motivation in Sangihe Regency Benefits of this research is to increase the knowledge in the field of human resource development for agricultural extension woker to increase the working productivity of extension woker and their institution.Data taken are primary data using questionnaire based interview techniques and using a Likert Scala and secondary data obtained from the Implementing Agency of Agricultural Fisheries andForesty Extesion (BP4K). Samples takenare so respondens spread in 5 (five)Implementing Agency (bp3k) Tahuna SubDistrict, East Tahuna Sub District, WestTahuna Sub district, Kendahe sub districtand North Tabukan sub disttict.Data are using regression analysis. Thisstudy is conducted over three monthsstarting from the Month of June 2013 toagustus 2013.The results of this research showed thateducation skills, discipline work ethosnumber of extension and motivation wassignificantly affected the performance ofagricultural extension officers in theSangihe Islands Regency